A possible role of stem cells in nasal polyposis. Issue 12 (3rd July 2017) - Klimek, L.; Koennecke, M.; Mullol, J.; Hellings, P. W.; Wang, D.Y.; Fokkens, W.; Gevaert, P.; Wollenberg, B.
Abstract: Since its discovery, the understanding of stem/progenitor cells raised dramatically in the last decade. Their regenerative potential is important to develop new therapeutic applications, but the identification advanced much faster than our understanding of stem/progenitor cells. In nasal polyposis, little is known about stem cells/progenitor cells and their ability. However, the further characterization of stem cells/progenitor cells may provide new treatment options for combating nasal polyposis. This review highlights the knowledge of the current literature about stem cells/progenitor cells in nasal polyposis and how this may be exploited in the development of novel treatment strategies.